Responsabilisation des femmes enceintes et soins différenciés dans le suivi médical du diabète de grossesse - Aurélie Racioppi (Anthropologie & Santé)
This article is based on doctoral research on the medical surveillance of pregnant women with gestational diabetes (DG) in two public maternity hospitals of the Ile-de-France region. In the context of the medicalization of pregnancy and of intensive DG screening, I compare the specificities of diabetes care in two maternity wards and analyze how these can lead to differentiated care. Although variable, these specificities of care rely greatly on pregnant women’s “compliance”. For healthcare professionals, ensuring their patients’ compliance involves transferring care. This transfer allows professionals to control the risks related to the disease, but also to relieve the maternity and diabetes services of the hospital. It relies on women being autonomous in their care, which is more difficult for women from underprivileged backgrounds. The latter must then compensate for institutional flaws such as the lack of access to a translator or the lack of alternatives to digital tracking, which represent a barrier to their access to quality care.